Evaluation of the nutritional potential of farmed Atlantic salmon (Salmo salar) tissues based on the contents of essential fatty acids - Thu Thi Hoai Mai; Jaeseok Choi; Donghwan Park; Sung-oh Park; Hekap Kim (Aquaculture Reports, 2024)
The aim of this study was to improve the extraction efficiency of lipids from ten Atlantic salmon tissues (spleen, viscera, gall bladder, heart, pyloric caeca, liver, head, ovary, eggs, and muscle) using solvents with low toxicity. The nutritional potential of lipids was evaluated based on their fatty acid (FA) contents, which were determined using gas chromatography-mass spectrometry (GC-MS). The FAs were derivatized with 10% H2SO4 in methanol to produce fatty acid methyl esters (FAMEs). A longer derivatization time led to a higher conversion efficiency of FAs to FAMEs. The contents of eicosapentaenoic acid (20:5 ω-3, EPA) and docosahexaenoic acid (22:6 ω-3, DHA) in all tissues ranged from 2.86 (0.15) to 92.2 (2.12) mg/g. The highest contents of both EPA and DHA were found in the ovary, followed by the eggs. The ratios of ω-6 to ω-3 polyunsaturated fatty acids (PUFAs) in all tissues were typically in the range of 0.27–2.23, indicating that salmon tissues were nutritionally beneficial. The proportions of ω-3 PUFA in the total lipids of all the by-products (except for the eggs) were lower than that in the muscle. However, the contents of ω-3 PUFAs in the liver, viscera, pyloric caeca, ovary, and eggs were two to five times higher than those in the muscle. The analysis showed the potential value of salmon by-products in providing ω-3 FAs.